2008
DOI: 10.1111/j.1439-0507.2008.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral yeast carriage in HIV‐infected and non‐infected populations in Rosario, Argentina

Abstract: Summary The objectives of the present study were: (i) to assess the frequency of oral colonisation by Candida species in HIV‐positive patients and to compare it with a population of HIV‐negative individuals, (ii) to determine the prevalence of C. dubliniensis in both populations and (iii) to determine the susceptibility of C. dubliniensis and other Candida species isolated from HIV‐positive patients to the most commonly used antifungal agents. Oral samples were obtained from 101 HIV‐positive and 108 HIV‐negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
44
1
16

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 28 publications
9
44
1
16
Order By: Relevance
“…In this study, we found no difference in the CD4+ T-lymphocyte counts between patients positive or negative for oral carriage of yeast. Other studies have also found no correlation between CD4+ T-lymphocyte counts and yeast colonization 2,7,19,20 . On the other hand, BACK-BRITO et al 2 and YANG et al 40 observed significantly lower yeast counts in patients with a lower viral load (< 400 copies/mL), suggesting that viral load might be a higher risk factor for the occurrence of candidiasis as compared to the CD4+ T-lymphocyte count.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this study, we found no difference in the CD4+ T-lymphocyte counts between patients positive or negative for oral carriage of yeast. Other studies have also found no correlation between CD4+ T-lymphocyte counts and yeast colonization 2,7,19,20 . On the other hand, BACK-BRITO et al 2 and YANG et al 40 observed significantly lower yeast counts in patients with a lower viral load (< 400 copies/mL), suggesting that viral load might be a higher risk factor for the occurrence of candidiasis as compared to the CD4+ T-lymphocyte count.…”
Section: Discussionmentioning
confidence: 95%
“…LUQUE et al 20 also observed that 59% of Argentinian HIV-positive patients carried two or three different species of yeast in their oral cavity. C. albicans and C. glabrata were the most frequently identified combination of yeast infections in our study.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…While a slight decrease [34] or no effect [5,10] on oropharyngeal yeast colonization in patients receiving ART has been reported, other authors also observed a protective effect of ART treatment regimens [7,11]. On the other hand, higher oropharyngeal Candida carriage has been detected in ART-treated HIVinfected individuals [2].…”
Section: Discussionmentioning
confidence: 95%
“…Candida species are harmless colonizers of the gastrointestinal and reproductive tracts in 50% to 60% of healthy people with no symptoms of candidiasis [1,2]. In individuals infected with human immunodeficiency virus (HIV), the prevalence of asymptomatic colonization of oral mucous is higher, approaching 80% [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%